2002
DOI: 10.2172/801399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Design Concepts for Adaptive Wind Turbine Blades

Abstract: Sandia is a rnuitiprcgram laboratory operated by Sandi Corporation.h k h e e d tdartin Campany. for the United States hpartmant of q n e r g y under Contract DE-AC04-WAL85OM);""~ Approved tor public release; firmer dissemination unlimited. Issued by b d i a AbstractThe objectives of this work were to develop conceptual structural designs for an adaptive (bend-twist coupled) blade, to evaluate candidate design concepts, to identify constraints and/or concerns for manufacturing, load paths, and stress concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Based on the blade FEM calculation method (McKittrick et al, 2001), the equations from (30) to (32) were used to calculate the coupling controlled factor and stiffness of each blade section (Griffin, 2002), whilst, If all the parameters of each section are used to evaluate the overall aerodynamic performances of the wind turbine blade, it is too complex and inconvenient to fulfill the evaluation. Literature (Wetzel, 2005) reported that the aerodynamic performances in the region closer to the blade tip are more important.…”
Section: Evaluation Of Performances Considering Different Design Modelsmentioning
confidence: 99%
“…Based on the blade FEM calculation method (McKittrick et al, 2001), the equations from (30) to (32) were used to calculate the coupling controlled factor and stiffness of each blade section (Griffin, 2002), whilst, If all the parameters of each section are used to evaluate the overall aerodynamic performances of the wind turbine blade, it is too complex and inconvenient to fulfill the evaluation. Literature (Wetzel, 2005) reported that the aerodynamic performances in the region closer to the blade tip are more important.…”
Section: Evaluation Of Performances Considering Different Design Modelsmentioning
confidence: 99%
“…Concepts such as active variable diameter rotors, bend-twist coupled blades, two-bladed rotors, or active control surfaces could have a higher economic value offshore, as long as they can also contribute to higher reliability (Energy Unlimited 2006;TPI Composites 2003a;Griffin 2002). Structural loads caused by turbulence can be reduced using both passive and active controls to allow for longer blades and greater swept area, which can benefit both land-based and offshore turbines.…”
Section: Advanced Rotors and Towersmentioning
confidence: 99%
“…power rating and height) is logistical in terms of transporting the large and heavy parts and assembling them by crane. Thus, an adaptable turbine blade design has been proposed that does not need motors for pitch control, but can have bend-twist coupling as needed when the blades spin too quickly [Eisler and Veers, 1998;Griffin, 2002]. This causes the blades to extract less power from the wind due to the bending moments pitching the blade out of the wind.…”
Section: Adaptive and Smart Structuresmentioning
confidence: 99%